Diversity and Abundance of Phytoplankton in the Coastal Waters of South Sulawesi - Hasriani Ayu Lestari; M. Farid Samawi; Ahmad Faizal; Abigail Mary Moore; Jamaluddin Jompa (Bogor Agricultural University, Indonesia, 2021)
Phytoplankton are primary producers that can be used as seawater condition indicators. Certain phytoplankton can proliferate, causing harmful algal blooms (HABs). The coastal waters of South Sulawesi, Indonesia are under pressure from land-based processes and activities resulting in inputs of organic and inorganic materials. This study analysed phytoplankton diversity and abundance in coastal waters around South Sulawesi. Phytoplankton were sampled and seawater parameters (salinity, temperature, turbidity, pH, nitrate concentration) measured in-situ at six stations around seven major river estuaries in three seaways (Makassar Strait, Flores Sea, Gulf of Bone). Phytoplankton taxonomic composition, abundance and indices of diversity (H’), evenness (E), and dominance (D) were analysed. Phytoplankton from 31 species and three classes (Bacillariophyceae, Cyanophyceae, Dinophyceae) were identified. Phytoplankton abundance and community structure differed significantly between sites and seaways but were not significantly correlated with water quality parameters although Dinophyceae abundance correlated significantly with observed pollution levels. Phytoplankton abundance was strongly influenced by the Dinophyceae, especially Ceratium furca, a potential HAB species; Cyanophyceae had the strongest influence on species richness but least on community structure. C. furca abundance was strongly correlated negatively with species richness, H’ and E, and positively with D, indicating negative impacts of this species on phytoplankton communities.